Modification treatment process of carbon fibers
Through the carbon fiber modification treatment process, including pretreatment, introduction and fixation of nanomaterials, surface treatment and mixing of multifunctional modifiers, the problems of uneven surface modification of carbon fiber and insufficient adhesion of nanomaterials are solved, significantly improving the mechanical properties and dispersion of carbon fibers, and meeting the needs of high-performance composite materials.
Patent Information
- Application Number
- CN202510708665.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-29
- Publication Date
- 2025-09-02
AI Technical Summary
The existing carbon fiber surface modification technology has problems such as uneven surface treatment, insufficient adhesion of nanomaterials and limited comprehensive performance improvement, making it difficult to meet the needs of high-performance composite materials.
The modification treatment process of carbon fiber is adopted, including pretreatment, introduction and fixation of nanomaterials, surface treatment and mixing of multifunctional modifiers. The surface uniformity and adhesion are ensured through ultrasonic cleaning, high-temperature reduction, gas-phase oxidation, composite biological enzyme cleaning, nanomaterial deposition and the use of multifunctional modifiers.
It significantly improves the mechanical properties, interface bonding and dispersion of carbon fibers, provides a comprehensive modification process, enhances the interface bonding and dispersion of carbon fibers and matrix materials, and improves the overall performance of composite materials.
Smart Images

Figure FT_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field related to carbon fiber production and processing, and specifically relates to a modification process of carbon fiber. Background Art
[0002] Carbon fiber, due to its high strength, low density, high modulus, and good corrosion resistance, is widely used in aerospace, automotive, sporting goods, electronic equipment, and biomedicine. However, the surface properties of carbon fiber, such as hydrophobicity and low surface energy, limit its application in certain composite materials, especially in scenarios requiring high interfacial bonding and good dispersion.
[0003] To improve the performance of carbon fibers in composite materials, surface modification technology has become a research hotspot. The goal of surface modification is to enhance the surface activity of carbon fibers, improve their interfacial bonding with the matrix material, and improve their dispersion within the composite material, thereby enhancing the overall performance of the composite material. Common surface modification methods include physical and chemical methods.
[0004] Although the existing carbon fiber surface modification technology has made some progress, there are still some limitations:
[0005] Uneven surface treatment: Traditional surface treatment methods may not evenly cover the carbon fiber surface, resulting in inconsistent modification effects.
[0006] Insufficient adhesion of nanomaterials: When introducing nanomaterials, existing fixing methods may not ensure the strong adhesion of nanomaterials on the carbon fiber surface, affecting the performance of the composite material.
[0007] Limited improvement in overall performance: Existing modification methods have limited effects in improving the mechanical properties, interfacial bonding strength and dispersibility of carbon fibers, and are unable to meet the demands of high-performance composite materials. Summary of the Invention
[0008] In view of the above problems, the present invention provides a modification process for carbon fiber to solve the technical problems in the background technology.
[0009] To achieve the above object, the technical solution adopted by the present invention is: The modification process of carbon fiber includes the following steps: S1: Pretreatment of carbon fiber powder, cleaning and drying of recycled carbon fiber powder, and surface pretreatment; S2: Introduction and fixation of nanomaterials, uniformly dispersing the nanomaterials on the surface of the carbon fiber powder and fixing them by physical or chemical methods; the nanomaterials include carbon nanotubes, graphene or nano-titanium dioxide, and the nanomaterials can be introduced and fixed by anodic electrophoretic deposition technology, chemical grafting method or plasma treatment method; S3: Surface treatment, using silane coupling agent, oxidant or other chemical reagents to treat the surface of carbon fiber powder; S4: Mix the multifunctional modifier with the carbon fiber powder and disperse it by mechanical stirring or ultrasonication to ensure uniform distribution; S5: Conduct mechanical property, interface bonding strength and dispersibility tests on the modified carbon fiber powder to verify the modification effect.
[0010] As a further improvement of the above scheme, the recovered carbon fiber powder is ultrasonically cleaned in S1 to remove grease and impurities on the surface; then it is subjected to high-temperature reduction treatment in a hydrogen or argon environment.
[0011] As a further improvement to the above scheme, after the cleaning and high-temperature reduction treatment in S1, a gas phase oxidation method is used to oxidize the carbon fiber powder using a gas medium such as ozone or carbon dioxide, and to etch the surface to form micropores or grooves.
[0012] As a further improvement of the above scheme, the pretreatment of the carbon fiber powder includes the following steps: treating the carbon fiber powder with a composite bio-enzyme cleaning agent, wherein the composite bio-enzyme cleaning agent contains cellulase, protease and lipase; and treating the carbon fiber surface with a nano-photocatalyst in collaboration with the bio-enzyme under visible light irradiation.
[0013] As a further improvement of the above scheme, anodic electrophoretic deposition technology is used in step S2. In step S2, a multi-field coupled deposition technology is used to prepare a nanomaterial coating on the carbon fiber surface. The technology combines electric field, magnetic field and ultrasonic field to synergistically disperse and fix the nanomaterial on the carbon fiber surface.
[0014] As a further improvement to the above solution, in S3, a surface grafting method is used after the surface treatment, and polymer chains are grafted on the surface of the carbon fiber powder using sodium polystyrene sulfonate.
[0015] As a further improvement of the above scheme, in step S3, it further includes using a bio-based surfactant to treat the carbon fiber powder, wherein the bio-based surfactant is a saponin surfactant prepared from natural plant extracts by a green chemical method, and the natural plant extracts include soybean extract, licorice extract, ginseng extract, tea tree extract, coconut extract or beet extract, which is used to enhance the hydrophilicity and biocompatibility of the carbon fiber powder surface.
[0016] As a further improvement of the above solution, the multifunctional modifier in S4 is a multifunctional polymer containing carboxyl, hydroxyl and amino groups; the multifunctional modifier is polyacrylic acid, polyvinyl alcohol, polyethylene glycol, sodium polystyrene sulfonate or a complex thereof.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. This invention provides a comprehensive carbon fiber modification process, encompassing a complete flow from pretreatment to final performance testing. By sequentially cleaning and drying the carbon fiber powder, introducing and fixing the nanomaterial, surface treating it, mixing it with a multifunctional modifier, and finally testing its performance, this process significantly improves the mechanical properties, interfacial bonding strength, and dispersibility of the carbon fiber.
[0019] 2. Ultrasonic cleaning in step S2 of the present invention: Through the cavitation effect of ultrasound, grease and impurities on the surface of the carbon fiber can be effectively removed, providing a clean surface for subsequent treatment.
[0020] High-temperature reduction treatment: High-temperature reduction treatment in a hydrogen or argon environment can restore the original structure of carbon fiber and improve its surface activity.
[0021] Gas phase oxidation treatment: Oxidation treatment using gas media such as ozone or carbon dioxide can etch micropores or grooves on the carbon fiber surface, increase surface roughness and specific surface area, and thus improve the adhesion of subsequent nanomaterials.
[0022] These pretreatment steps provide better surface conditions for the photocatalytic cleaning technology of composite bio-enzyme cleaning agents and nano-photocatalysts, allowing subsequent treatments to be carried out more effectively.
[0023] Composite bio-enzyme cleaning agent: A composite system containing cellulase, protease and lipase, which can efficiently decompose organic pollutants on the surface of carbon fiber under mild conditions while maintaining the structural integrity of carbon fiber.
[0024] Synergistic effect: Ultrasonic cleaning and high-temperature reduction treatment have preliminarily cleaned the carbon fiber surface, while the composite bio-enzyme cleaning agent can further remove residual organic pollutants, ensuring a cleaner surface and providing better conditions for the subsequent introduction and fixation of nanomaterials.
[0025] 3. In the present invention, in step S2, nano-titanium dioxide is mixed with the nano-material to form a composite nano-material. The nano-titanium dioxide is evenly dispersed on the surface of the carbon fiber powder by chemical grafting or physical adsorption.
[0026] In step S3, sodium polystyrene sulfonate is used to perform surface grafting treatment on the carbon fiber powder.
[0027] At the same time, the photocatalytic properties of nano-titanium dioxide are utilized, and ultraviolet light treatment is used to further enhance the chemical activity and weather resistance of the carbon fiber surface. Nano-titanium dioxide has photocatalytic properties, which can decompose organic pollutants under ultraviolet light, enhancing the weather resistance and self-cleaning ability of the carbon fiber surface. The high hardness and good dispersibility of nano-titanium dioxide can further improve the mechanical properties of carbon fiber composites, such as tensile strength and modulus.
[0028] The synergistic effect of sodium polystyrene sulfonate and nano-titanium dioxide can improve the surface hydrophilicity and dispersibility of carbon fiber, while enhancing the interfacial bonding force with the resin matrix.
[0029] 4. In step S3, the present invention further includes treating the carbon fiber powder with a bio-based surfactant, which is prepared from natural plant extracts using green chemistry methods and has excellent hydrophilicity and biocompatibility. Treating the carbon fiber powder with this surfactant significantly enhances the hydrophilicity and biocompatibility of the fiber surface while maintaining environmental friendliness. This naturally derived surfactant not only improves the performance of the carbon fiber but also meets current requirements for green chemistry and sustainable development.
[0030] 5. The multifunctional modifier in the present invention generally refers to a polymer or composite material having multiple functional groups, which can chemically bond with the surface of carbon fibers, thereby enhancing the surface properties of the carbon fibers and the interfacial bonding strength with the matrix material. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The present invention provides a comparative table of experimental data on the performance improvement of Examples 1 to 4 and the prior art in carbon fiber modification treatment. DETAILED DESCRIPTION
[0032] In order to enable those skilled in the art to better understand the technical solution, the present invention is described in detail below in conjunction with embodiments. The description in this section is only exemplary and explanatory and should not have any limiting effect on the scope of protection of the present invention.
[0033] The specific solution of this application is: a carbon fiber modification process, comprising the following steps: S1: Pretreatment of carbon fiber powder, cleaning and drying of recycled carbon fiber powder, and surface pretreatment; S2: Introduction and fixation of nanomaterials: uniformly dispersing the nanomaterials on the surface of the carbon fiber powder and fixing them by physical or chemical methods; nanomaterials include carbon nanotubes, graphene or nano-titanium dioxide, and the nanomaterials can be introduced and fixed by anodic electrophoretic deposition technology, chemical grafting or plasma treatment; S3: Surface treatment, using silane coupling agent, oxidant or other chemical reagents to treat the surface of carbon fiber powder; S4: Mix the multifunctional modifier with the carbon fiber powder and disperse it by mechanical stirring or ultrasonication to ensure uniform distribution; S5: Conduct mechanical property, interface bonding strength and dispersibility tests on the modified carbon fiber powder to verify the modification effect.
[0034] As a preferred embodiment of the above embodiment, in S1, the recovered carbon fiber powder is ultrasonically cleaned to remove grease and impurities on the surface; and then a high-temperature reduction treatment is performed in a hydrogen or argon environment.
[0035] As a preferred embodiment of the above, after the cleaning and high-temperature reduction treatment in S1, the carbon fiber powder is oxidized by gas phase oxidation using a gas medium such as ozone or carbon dioxide to etch the surface to form micropores or grooves.
[0036] As a preferred embodiment of the above embodiment, the pretreatment of carbon fiber powder includes the following steps: treating the carbon fiber powder with a composite bio-enzyme cleaning agent, the composite bio-enzyme cleaning agent containing cellulase, protease and lipase; and treating the carbon fiber surface with a nano-photocatalyst in collaboration with the bio-enzyme under visible light irradiation.
[0037] As a preferred method of the above embodiment, anodic electrophoretic deposition technology is used in step S2. In step S2, a multi-field coupled deposition technology is used to prepare a nanomaterial coating on the carbon fiber surface. The technology combines electric field, magnetic field and ultrasonic field, and the nanomaterial is evenly dispersed and fixed on the carbon fiber surface through synergistic action.
[0038] As a preferred embodiment of the above embodiment, after the surface treatment in S3, a surface grafting method is used to graft polymer chains on the surface of the carbon fiber powder using sodium polystyrene sulfonate. As a preferred embodiment of the above embodiment, in step S3, the carbon fiber powder is further treated with a bio-based surfactant, which is a saponin surfactant prepared from natural plant extracts by green chemical methods. The natural plant extracts include soybean extract, licorice extract, ginseng extract, tea tree extract, coconut extract or beet extract, which is used to enhance the hydrophilicity and biocompatibility of the carbon fiber powder surface.
[0039] As a preferred embodiment of the above embodiment, the multifunctional modifier in S4 is a multifunctional polymer containing carboxyl, hydroxyl and amino groups; the multifunctional modifier is polyacrylic acid, polyvinyl alcohol, polyethylene glycol, sodium polystyrene sulfonate or a complex thereof.
[0040] Example 1: Ultrasonic cleaning and high temperature reduction treatment Experimental steps: S1: Pretreatment of carbon fiber powder Ultrasonic cleaning: The recycled carbon fiber powder is placed in an ultrasonic cleaner and cleaned with deionized water for 30 minutes at a frequency of 40kHz to remove grease and impurities on the surface.
[0041] High-temperature reduction treatment: The cleaned carbon fiber powder is subjected to high-temperature reduction treatment in a hydrogen atmosphere at a temperature of 800°C for 2 hours to restore the original structure of the carbon fiber.
[0042] S2: Introduction and immobilization of nanomaterials Anodic electrophoretic deposition: Anodic electrophoretic deposition is used to deposit a carbon nanotube coating on the carbon fiber surface. The electrophoretic solution is composed of carbon nanotubes and nanocellulose, the voltage is 100V, and the deposition time is 15 minutes.
[0043] S3: Surface treatment Silane coupling agent treatment: The carbon fiber powder is surface treated with a silane coupling agent for 1 hour.
[0044] S4: Mixing of multifunctional modifiers Polyacrylic acid mixing: Polyacrylic acid is mixed with carbon fiber powder as a multifunctional modifier, and mechanical stirring is used to ensure uniform distribution. The stirring time is 30 minutes.
[0045] S5: Performance Test Mechanical properties test: A universal material testing machine was used to test the tensile strength and elastic modulus of the modified carbon fiber powder.
[0046] Interface bonding strength test: The microdroplet method was used to test the interface shear strength between the modified carbon fiber powder and epoxy resin.
[0047] Dispersion test: Dynamic light scattering was used to measure the dispersibility of the modified carbon fiber powder in aqueous solution.
[0048] Beneficial effects: 1. High surface cleanliness: Ultrasonic cleaning can effectively remove grease and impurities on the surface of carbon fiber, ensure surface cleanliness, and provide a good foundation for subsequent processing.
[0049] 2. Structural recovery: High-temperature reduction treatment is carried out in a hydrogen or argon environment, which can restore the original structure of carbon fiber and improve its conductivity and mechanical properties.
[0050] 3. Enhanced adhesion: The introduction of carbon nanotubes through anodic electrophoretic deposition technology significantly improves the adhesion of nanomaterials on the carbon fiber surface and enhances the interfacial bonding strength of the composite material.
[0051] 4. Uniform dispersion: The surface treatment of silane coupling agent and the mixing of multifunctional modifier of polyacrylic acid ensure the uniform dispersion of nanomaterials and modifiers on the surface of carbon fiber, thus improving the overall performance of the composite material.
[0052] Example 2: Gas-phase oxidation treatment and composite enzyme cleaning agent Experimental procedures S1: Pretreatment of carbon fiber powder Ultrasonic cleaning: The recycled carbon fiber powder is placed in an ultrasonic cleaner and cleaned with deionized water for 30 minutes at a frequency of 40kHz to remove grease and impurities on the surface.
[0053] High-temperature reduction treatment: The cleaned carbon fiber powder was subjected to high-temperature reduction treatment in an argon atmosphere at a temperature of 800°C for 2 hours.
[0054] Gas phase oxidation treatment: The carbon fiber powder is oxidized by using ozone (concentration of 100 ppm) using a gas phase oxidation method to etch the surface to form micropores or grooves. The treatment time is 1 hour.
[0055] Composite enzyme cleaning agent treatment: The carbon fiber powder was treated with a composite enzyme cleaning agent (containing cellulase, protease, and lipase) for one hour. Under visible light irradiation (wavelength of 450nm), the carbon fiber surface was treated with a nano-photocatalyst (titanium dioxide) in conjunction with the enzyme for two hours.
[0056] S2: Introduction and immobilization of nanomaterials Multi-field coupled deposition technology: Graphene coatings were deposited on carbon fiber surfaces using a multi-field coupled deposition technique (combining electric, magnetic, and ultrasonic fields). The electric field strength was 1000 V / m, the magnetic field strength was 0.5 T, the ultrasonic frequency was 40 kHz, and the deposition time was 30 minutes.
[0057] S3: Surface treatment Sodium polystyrene sulfonate grafting: Sodium polystyrene sulfonate was used to treat the surface of the carbon fiber powder, and the grafting time was 2 hours.
[0058] S4: Mixing of multifunctional modifiers Polyvinyl alcohol mixing: Polyvinyl alcohol is mixed with carbon fiber powder as a multifunctional modifier, and ultrasonic dispersion is used to ensure uniform distribution. The dispersion time is 30 minutes.
[0059] S5: Performance Test Mechanical properties test: A universal material testing machine was used to test the tensile strength and elastic modulus of the modified carbon fiber powder.
[0060] Interface bonding strength test: The microdroplet method was used to test the interface shear strength between the modified carbon fiber powder and epoxy resin.
[0061] Dispersion test: Dynamic light scattering was used to measure the dispersibility of the modified carbon fiber powder in aqueous solution.
[0062] Beneficial effects 1. Enhanced surface activity: Gas phase oxidation treatment etches the carbon fiber surface through ozone or carbon dioxide to form micropores or grooves, which increases the surface active sites and improves the adhesion of nanomaterials.
[0063] 2. Synergistic effect of bio-enzymes: The composite bio-enzyme cleaning agent (cellulase, protease and lipase) combined with the photocatalytic effect of nano-photocatalysts further cleans the surface and introduces active functional groups, enhancing the surface hydrophilicity and biocompatibility.
[0064] 3. Multi-field coupling technology: The graphene coating is prepared using multi-field coupling deposition technology (electric field, magnetic field and ultrasonic field), which significantly improves the uniformity and adhesion of the coating, and enhances the temperature resistance of carbon fiber and its bonding ability with resin.
[0065] 4. Performance improvement: The surface grafting of sodium polystyrene sulfonate and the mixing of the multifunctional modifier of polyvinyl alcohol further improve the surface hydrophilicity and dispersibility of carbon fibers and improve the overall performance of the composite material.
[0066] Example 3: Bio-based surfactants and multifunctional polymer modifiers Experimental procedures S1: Pretreatment of carbon fiber powder Ultrasonic cleaning: The recycled carbon fiber powder is placed in an ultrasonic cleaner and cleaned with deionized water for 30 minutes at a frequency of 40kHz to remove grease and impurities on the surface.
[0067] High-temperature reduction treatment: The cleaned carbon fiber powder is subjected to high-temperature reduction treatment in a hydrogen atmosphere at a temperature of 800°C for 2 hours.
[0068] S2: Introduction and immobilization of nanomaterials Plasma treatment: Plasma treatment was used to fix nano-titanium dioxide on the carbon fiber surface. The plasma treatment time was 10 minutes and the power was 100W.
[0069] S3: Surface treatment Bio-based surfactant treatment: The carbon fiber powder was treated with a bio-based surfactant (saponin surfactant prepared from soybean extract) for 1 hour to enhance the surface hydrophilicity and biocompatibility.
[0070] S4: Mixing of multifunctional modifiers Polyethyleneimine mixing: Polyethyleneimine as a multifunctional modifier is mixed with carbon fiber powder and mechanical stirring is used to ensure uniform distribution. The stirring time is 30 minutes.
[0071] S5: Performance Test Mechanical properties test: A universal material testing machine was used to test the tensile strength and elastic modulus of the modified carbon fiber powder.
[0072] Interface bonding strength test: The microdroplet method was used to test the interface shear strength between the modified carbon fiber powder and epoxy resin.
[0073] Dispersion test: Dynamic light scattering was used to measure the dispersibility of the modified carbon fiber powder in aqueous solution.
[0074] Beneficial effects 1. Environmental protection: The use of bio-based surfactants (such as saponin surfactants in soybean extracts) for surface treatment meets the requirements of green chemistry and reduces the impact on the environment.
[0075] 2. Biocompatibility: The use of bio-based surfactants significantly improves the biocompatibility of carbon fiber, making it more suitable for use in the fields of biomedicine and environmentally friendly materials.
[0076] 3. Strong adhesion: The plasma treatment method fixes nano-titanium dioxide and combines it with the multifunctional modifier of polyethyleneimine to significantly improve the adhesion of nano-materials and the interfacial bonding strength of composite materials.
[0077] 4. Performance optimization: By mixing with multifunctional polymer modifiers, the surface properties of carbon fiber are further optimized, and its dispersion and mechanical properties in composite materials are improved.
[0078] Example 4: Modification of sodium polystyrene sulfonate and nano-titanium dioxide Purpose of the experiment This embodiment aims to enhance the surface hydrophilicity, biocompatibility and mechanical properties of carbon fiber powder through the synergistic effect of sodium polystyrene sulfonate and nano-titanium dioxide, while improving its dispersibility and interfacial bonding strength in the composite material.
[0079] Experimental procedures S1: Pretreatment of carbon fiber powder Ultrasonic cleaning: The recycled carbon fiber powder is placed in an ultrasonic cleaner and cleaned with deionized water for 30 minutes at a frequency of 40kHz to remove grease and impurities on the surface.
[0080] High-temperature reduction treatment: The cleaned carbon fiber powder is subjected to high-temperature reduction treatment in a hydrogen atmosphere at a temperature of 800°C for 2 hours to restore the original structure of the carbon fiber.
[0081] S2: Introduction and immobilization of nanomaterials Introduction of nano-titanium dioxide: Plasma treatment is used to fix nano-titanium dioxide on the surface of carbon fiber. The carbon fiber powder is placed in the plasma treatment equipment, the power is set to 100W, and the treatment time is 10 minutes.
[0082] Grafting of sodium polystyrene sulfonate: The treated carbon fiber powder was dispersed in an aqueous solution containing sodium polystyrene sulfonate at a PSS concentration of 1 wt% and the grafting time was 2 hours. PSS was evenly grafted onto the carbon fiber surface through a chemical grafting method.
[0083] S3: Surface treatment Surface grafting method: Carbon fiber powder is surface treated with sodium polystyrene sulfonate. The carbon fiber powder is dispersed in a sodium polystyrene sulfonate solution at a concentration of 1wt% for 2 hours. The sodium polystyrene sulfonate is grafted onto the carbon fiber surface through chemical bonding.
[0084] S4: Mixing of multifunctional modifiers Mixing of multifunctional modifiers: A multifunctional polymer containing carboxyl, hydroxyl, and amino groups (e.g., polyvinyl alcohol (PVA)) is mixed with the carbon fiber powder. A 5wt% PVA solution is mixed with the carbon fiber powder and ultrasonically dispersed for 30 minutes to ensure uniform distribution.
[0085] S5: Performance Test Mechanical properties test: A universal material testing machine was used to test the tensile strength and elastic modulus of the modified carbon fiber powder.
[0086] Interface bonding strength test: The microdroplet method was used to test the interface shear strength between the modified carbon fiber powder and epoxy resin.
[0087] Dispersion test: Dynamic light scattering was used to measure the dispersibility of the modified carbon fiber powder in aqueous solution.
[0088] Experimental results analysis Improved mechanical properties: The synergistic effect of sodium polystyrene sulfonate and nano-titanium dioxide significantly improves the tensile strength and elastic modulus of carbon fibers. The fixation of sodium polystyrene sulfonate and nano-titanium dioxide enhances the chemical activity of the carbon fiber surface, thereby improving its mechanical properties in the composite material.
[0089] Enhanced interfacial bonding: The synergistic effect of sodium polystyrene sulfonate and nano-titanium dioxide significantly improves the interfacial bonding between carbon fiber and epoxy resin. The nano-size effect of titanium dioxide and the hydrophilicity of sodium polystyrene sulfonate work together to enhance the interaction between carbon fiber and resin.
[0090] Improved dispersibility: Grafting of sodium polystyrene sulfonate significantly improves the dispersibility of carbon fiber powder in aqueous solutions. The hydrophilic functional groups of sodium polystyrene sulfonate reduce the agglomeration of carbon fibers, thereby improving their dispersibility in composite materials.
[0091] Beneficial effects: 1. Enhanced surface hydrophilicity: The grafting of sodium polystyrene sulfonate significantly improves the hydrophilicity of the carbon fiber surface, reduces the agglomeration phenomenon in aqueous solutions, and improves dispersibility.
[0092] 2. Improved biocompatibility: Grafting of sodium polystyrene sulfonate also enhances the biocompatibility of carbon fiber, making it more suitable for biomedical applications.
[0093] 3. Enhanced adhesion: The introduction of nano-titanium dioxide is fixed on the surface of carbon fiber through plasma treatment, which significantly improves the adhesion of nanomaterials and enhances the interfacial bonding strength of composite materials.
[0094] 4. Performance improvement: Through the synergistic effect of sodium polystyrene sulfonate and nano-titanium dioxide, the tensile strength, elastic modulus and interfacial shear strength of carbon fiber are significantly improved, while its dispersion in the composite material is improved.
[0095] In this embodiment, the mechanical properties, interfacial bonding strength and dispersibility of carbon fiber powder are significantly improved through the synergistic modification of sodium polystyrene sulfonate and nano-titanium dioxide.
[0096] The performance improvement of Examples 1 to 4 in carbon fiber modification treatment was compared with the prior art. Figure 1 The data in the table will show the experimental data of each embodiment and compare it with the prior art to highlight the improvements and advantages of each embodiment.
[0097] It should be noted that, in this article, the terms include, comprise or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device comprising a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. Specific examples are used herein to illustrate the principles and implementation methods of the technical solution of the present invention. The above examples are only used to help understand the method of the present invention and its core idea. The above is only a preferred embodiment of the present invention. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, ordinary technicians in this technical field can make several improvements, modifications or changes without departing from the principles of the present invention, and can also combine the above technical features in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the inventive concept and technical solution to other occasions without improvement, should all be regarded as the scope of protection of the present invention.
Claims
1. A modification process for carbon fiber, characterized in that: The following steps are involved: S1: Pretreatment of carbon fiber powder, cleaning and drying of recycled carbon fiber powder, and surface pretreatment; S2: Introduction and fixation of nanomaterials, uniformly dispersing the nanomaterials on the surface of the carbon fiber powder and fixing them by physical or chemical methods; the nanomaterials include carbon nanotubes, graphene or nano-titanium dioxide, and the nanomaterials are introduced and fixed by anodic electrophoretic deposition technology, chemical grafting or plasma treatment; S3: Surface treatment, using silane coupling agent, oxidant or other chemical reagents to treat the surface of carbon fiber powder; S4: Mix the multifunctional modifier with the carbon fiber powder and disperse it by mechanical stirring or ultrasonication to ensure uniform distribution; S5: Conduct mechanical property, interface bonding strength and dispersibility tests on the modified carbon fiber powder to verify the modification effect.
2. The carbon fiber modification process according to claim 1, characterized in that: In S1, the recovered carbon fiber powder is ultrasonically cleaned to remove grease and impurities on the surface; then it is subjected to high-temperature reduction treatment in a hydrogen or argon environment.
3. The carbon fiber modification process according to claim 2, characterized in that: After the cleaning and high-temperature reduction treatment in S1, the carbon fiber powder is oxidized by a gas phase oxidation method using ozone or carbon dioxide gas medium to etch the surface to form micropores or grooves.
4. The carbon fiber modification process according to claim 1, characterized in that: The pretreatment of the carbon fiber powder includes the following steps: treating the carbon fiber powder with a composite bio-enzyme cleaning agent, wherein the composite bio-enzyme cleaning agent contains cellulase, protease and lipase; and treating the carbon fiber surface with a nano-photocatalyst in coordination with the bio-enzyme under visible light irradiation.
5. The carbon fiber modification process according to claim 1, characterized in that: In step S2, anodic electrophoretic deposition technology is used. In step S2, a nanomaterial coating is prepared on the surface of the carbon fiber, and the nanomaterial is evenly dispersed and fixed on the surface of the carbon fiber by combining electric field, magnetic field and ultrasonic field.
6. The carbon fiber modification process according to claim 1, characterized in that: In S3, after the surface treatment, a surface grafting method is used to graft polymer chains on the surface of the carbon fiber powder using sodium polystyrene sulfonate.
7. The carbon fiber modification process according to claim 1, characterized in that: In step S3, the carbon fiber powder is further treated with a bio-based surfactant, wherein the bio-based surfactant is a saponin surfactant prepared from natural plant extracts by a green chemical method, and the natural plant extracts include soybean extract, licorice extract, ginseng extract, tea tree extract, coconut extract or beet extract, which is used to enhance the hydrophilicity and biocompatibility of the carbon fiber powder surface.
8. The carbon fiber modification process according to claim 1, characterized in that: The multifunctional modifier in S4 is a multifunctional polymer containing carboxyl, hydroxyl and amino groups; the multifunctional modifier is polyacrylic acid, polyvinyl alcohol, polyethylene glycol, sodium polystyrene sulfonate or a composite thereof.
Citation Information
Cited By
Green continuous preparation process of chemical modification reinforced composite material
CN121592052A